2014
DOI: 10.5999/aps.2014.41.6.647
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on Survival of the Composite Graft and the Proper Time of Injection in a Rabbit Ear Composite Graft Model

Abstract: BackgroundAdministration of growth factors has been associated with increased viability of composite grafts greater than 1-cm in diameter. Platelet-rich plasma (PRP) contains many of the growth factors studied. In this study, we evaluate the effect of PRP injection on composite graft viability and the proper time for injection.MethodsA total of 24 New Zealand White rabbits were divided into four groups. Autologous PRP was injected into the recipient sites three days before grafting in group 1, on the day of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Pallua et al [9] have reported that application of platelet-rich plasma for burn patients accelerates re-epithelization. In another study by Choi et al [10] , the subcutaneous injection of platelet rich plasma in a rabbit skin flap was shown to promote vasculogenesis and increase flap survival.…”
Section: Resultsmentioning
confidence: 97%
“…Pallua et al [9] have reported that application of platelet-rich plasma for burn patients accelerates re-epithelization. In another study by Choi et al [10] , the subcutaneous injection of platelet rich plasma in a rabbit skin flap was shown to promote vasculogenesis and increase flap survival.…”
Section: Resultsmentioning
confidence: 97%
“…However, unlike skin grafts, composite grafts have a layer of cartilage, which can act as a mechanical barrier that limits the vascularization of the wound bed. Thus, it is conceivable that revascularization via the dermis connection to the dermis at the wound edge is more important for the survival of the composite graft, and in turn limits the size of the composite graft [ 11 ]. Because it is like a skin graft, the viability of the composite graft is influenced by good recipient vascularity, accurate contact between the graft and recipient, and immobilization [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of VEGF in angiogenesis is as a specific mitogen factor for endothelial cells, which stimulates the formation of new blood vessels and increases their permeability. In PRP, there are many of the growth factors mentioned above which are proven to increase the viability of the composite graft [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets contain growth factors that stimulate neoangiogenesis and cell differentiation [5][6][7] . Platelets in PRP are obtained in anticoagulated state, therefore inert and require activation (usually accomplished by the addition of calcium chloride and / or thrombin) to release their growth factors 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The association of fat grafts and PRP began to be studied in recent years 7,14 . This association is justifiable due to the pursuit of PRP as a mechanism to improve the viability and quality of fat grafts, mainly by stimulating neovascularization of the grafts.…”
Section: Introductionmentioning
confidence: 99%